THE SEISMIC HAZARD DETERMINATION OF THE BUILDING SITE OF NSC "OLIMPIYSKIY" IN KYIV - KENDZERA, O.; SKLIAR, O.; LISOVYI, Yu.; KORNIIENKO, E.; SEMENOVA, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The research work by establishment of seismic hazard level (the improved value of seismic intensity taking into account the influencing of soil conditions) for National Sports Complex "Olimpiyskiy" site in Kyiv is conducted by S.I. Subbotin Institute of geophysics of the National Academy of Sciences of Ukraine. Three relatively homogeneous (in the seismic relation) taxonomic units on the territory of site are selected. The level of seismic safety in the balls of МSК-64 seismic intensity scale was set for each of this taxonomic units.